(untitled) (Journal of Bangladesh Academy of Sciences, 2021)
The serum level of zinc and vitamin E were measured to understand the association of various nutrients on acne pathogenesis. Both zinc and vitamin E are antioxidants used as a supplement in acne treatment. However, their effect and status in acne patients are not fully understood. This study included 48 acne patients and 48 sex- and age-matched healthy controls. The zinc and vitamin E concentration was measured in the serum by flame atomic absorption spectroscopy (AAS) and HPLC methods. Compared to the healthy control, a significant deficiency of serum vitamin E level in acne patients (p<0.001) was found, although the patients were not deficient in serum zinc level (p=0.22). In addition, female acne patients had a slightly lower zinc level than male patients (p=0.06). The low serum vitamin E level suggests that supplementation of vitamin E might be helpful in acne treatment. However, further studies are required to understand the dose and mechanism of vitamin E supplements in acne treatment. J. Bangladesh Acad. Sci. 45(1); 49-58: June 2021